Patrimonializarte: A Heritage Education Program Based on New Technologies and Local Heritage - Leticia Castro-Calviño; Jairo Rodríguez-Medina; Cosme J. Gómez-Carrasco; Ramón López-Facal (MDPI AG, 2020)
This paper presents the design of the Patrimonializarte program, which has been implemented in six classes and three different educational levels in two schools in Galicia (Spain). It involves working with elements of heritage in proximity to the schools' pupils by employing Information and Communication Technology (ICT) tools. The objectives are (a) to find out if the design is coherent and relevant according to expert judgement and (b) to discover whether the activities related with new technologies are effective according to the evaluation of those involved in the program. This is evaluation research employing mixed methods in which a collective study of cases is carried out. The main results show (1) the evaluation of the design and the tools of the program achieve an optimal degree of agreement according to the panel of experts as far as the variables measured are concerned, and (2) the schoolchildren and teaching staff provide a positive evaluation of the use of ICT tools for working with heritage. E-learning and m-learning make it possible to motivate pupils in the learning and teaching process. Working with ICT tools acquires importance with regard to the possibilities they offer to disseminate the heritage. An integral evaluation of programs is considered relevant in order to understand their multi-dimensionality.